Influence of Oxymethylene Ethers (OMEn) in Mixtures with a Diesel Surrogate - Sandra Richter; Trupti Kathrotia; Marina Braun-Unkhoff; Clemens Naumann; Markus Köhler (Energies, 2021)
Within this work the effects of blending oxymethylene ethers (OMEn) to a diesel surrogate (50 mol% n-dodecane, 30 mol% farnesane, and 20 mol% 1-methylnaphthalene) were investigated by performing two different types of experiments: measurements of the sooting propensity and of the laminar burning velocity, each in laminar premixed flames. For the sooting propensity, OME3, OME4, and OME5 were considered as blending compounds—each in mass fractions of 10%, 20%, and 30%. The sooting propensity was found to depend strongly on the OMEn blending grade but not on its chain length. In addition, the effect on the laminar burning velocity was studied for OME4 and the admixture of 30% OME4 with diesel surrogate for the first time. This admixture was found to lead to increased burning velocities; however, much less than might be foreseen when considering the respective values of the neat fuels.